Revision of the genus Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) in Australia - Shea, Glenn; Couper, Patrick; Wilmer, Jessica Worthington; Amey, Andrew (Zootaxa, 2011)
The gekkonid lizard genus Cyrtodactylus in Australia is revised based on a combination of morphology and mitochondrial (ND2) sequence data. Previous hypotheses that the Australian populations are assignable to a New Guinea species, C. louisiadensis, or to a Cyrtodactylus louisiadensis species group defined on shared colour pattern and enlarged subcaudal scales, are rejected. Evidence is provided for the existence of five endemic species in Australia, allopatrically distributed. Cyrtodactylus tuberculatus (Lucas & Frost) is formally resurrected for Australian populations in the Cooktown area, from Mt Leswell north to Stanley Island. Four new species are described: C. mcdonaldi sp. nov. in the south, from the Chillagoe area north to Parrot Creek Falls, C. hoskini sp. nov. from the Iron Range area, C. adorus sp. nov. from the Pascoe River drainage, and C. pronarus sp. nov. from the McIlwraith Range. Concordant genetic and morphological evidence enable the hypothesis that C. adorus and C. pronarus represent a species pair distinct from the sublineage represented by C. tuberculatus, C. mcdonaldi and C. hoskini.